2019
DOI: 10.1039/c8cs00369f
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor reactivity in glycosylation reactions

Abstract: The effect of the reactivity of the glycosyl acceptor on the outcome of glycosylation reactions is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(86 citation statements)
references
References 128 publications
5
81
0
Order By: Relevance
“…reported that acceptor reactivities were highly related to the stereochemical outcome of chemical glycosylation. [29] However,t he true behavior of na cceptor is hard to depictb ecause its nucleophilicity dependso nn umerous factors, including steric effects, inductive effects, and conformational effects. To gain an insight into the influencing factors of the acceptor,S eeberger et al [5] furthera pplied their automated glycosylation instrument to clarify the relationship between reactivity and stereoselectivity (Table 2).…”
Section: Systematic Studies Related To Glycosylationmentioning
confidence: 99%
“…reported that acceptor reactivities were highly related to the stereochemical outcome of chemical glycosylation. [29] However,t he true behavior of na cceptor is hard to depictb ecause its nucleophilicity dependso nn umerous factors, including steric effects, inductive effects, and conformational effects. To gain an insight into the influencing factors of the acceptor,S eeberger et al [5] furthera pplied their automated glycosylation instrument to clarify the relationship between reactivity and stereoselectivity (Table 2).…”
Section: Systematic Studies Related To Glycosylationmentioning
confidence: 99%
“…Regioselectivity responds to multiple steric and electronic factors present in both the glycosyl donor and acceptor, and they are characteristic for each particular sugar. Although relative reactivity values have been established for glycosyl donors, it has not been possible to do the same for glycosyl acceptors, whose relative reactivity is still rather poorly understood [6]. Regioselective approaches for the glycosylation of acceptors with more than one free hydroxy group have been developed, and in some of the cases they were successfully rationalized [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To address this stereoselectivity problem, we turned our attention to the inuence of glycosyl acceptor reactivity, as acceptor reactivities can signicantly impact stereoselectivities. [53][54][55] Two nucleophiles, i.e., ethanol 8b and tri-uoroethanol (TFE) 8c, were tested (Scheme 2). Glycosylation between 7 and the more reactive acceptor ethanol provided 9b with high yield and b-selectivity (a/b < 1:20), while less reactive acceptor TFE gave a slight preference for the a-anomer product (a/b ¼ 1.6/1).…”
Section: Synthesis Of the Glycosyl Dipeptide Cassettementioning
confidence: 99%